Systematic Literature Review: Utilization of Articulate Storyline-based Interactive Learning Media in Primary School Student Learning - Kurniasari, Winda; Sutopo, Yeri; Harianingsih, Harianingsih; Subali, Bambang; Widiarti, Nuni (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the utilization of Articulate Storyline-based interactive learning media in the context of learning in elementary schools through a Systematic Literature Review (SLR) approach. A total of 25 articles from national and international journals published between 2021 and 2025 were analyzed to identify the contribution of this media to improving students' learning outcomes, motivation, understanding, science literacy, and critical thinking skills. The results showed that Articulate Storyline can present learning materials interactively and engagingly through visual, audio, simulation, and self-evaluation features, thus creating an adaptive and meaningful learning experience. This media is proven effective in various subjects such as science, social studies, mathematics, Indonesian language, and Pancasila education for elementary school students. Despite its many benefits, implementation challenges such as infrastructure limitations and differences in student learning styles are still a concern. Therefore, further research is needed to explore solutions and expand the application of this media in various educational contexts. This study provides important recommendations for teachers and education practitioners in developing innovative digital learning media according to the needs and characteristics of learners in the digital era.